Mimbres Great Kivas and Plazas During the Three Circle Phase, ca. AD 850–1000†. Issue 3 (20th November 2015) - Creel, Darrell; Shafer, Harry J.
Abstract : Most Mimbres villages had a great kiva that opened onto and was accessed through a plaza area during the Three Circle phase. In the few cases where these plazas have been excavated, secondary cremations and related artifact caches were present in some quantity. Use of plazas for interment of cremated individuals continued into the Mimbres Classic period, although great kivas were no longer built and used. The plazas remained in use, still surrounded by buildings which were by then fully surface pueblos.